Keberlangsungan Pesantren: Tantangan dan Solusinya - Triasmoro, Longgar Wahyudi; Yamco, Marfiati; Aji, Pramana Wahyu (Research and Community Service UNIVERSITAS KALBIS, 2025)
The aim of this study is to identify the challenges faced by Islamic boarding schools (pesantren) and recommend solutions to ensure the sustainability of this oldest educational institution. This research employs a descriptive approach through qualitative and quantitative descriptive analysis. The sample consists of 210 respondents, including 66 students, 101 parents, and 43 teachers and administrators from the Baitul Hikmah Foundation in Sukoharjo Regency, Central Java Province. Data analysis was conducted using descriptive analysis with an empathy map. The results indicate that the main challenges are related to high education costs, lack of extracurricular activities, service quality, curriculum and teaching systems, and the overall quality of the pesantren. To address these issues, the pesantren requires strategic solutions, such as establishing business units to support stronger and more independent funding, offering more varied extracurricular activities, improving service quality, reviewing the curriculum and teaching systems, and implementing strategies to enhance the quality of the pesantren.This study has limitations, as it only sampled 210 internal respondents from one pesantren. Future research should expand the sample size across multiple pesantren and include other stakeholders.